Koperasi Serba Usaha Baringin Siduampan (KSU-BS) Kecamatan Ranah Batahan Kabupaten Pasaman Barat Tahun 1999-2018 - Sisri Manda Sari; Azmi Fitrisia (Jurusan Sejarah FIS UNP, 2019)
Koperasi Serba Usaha Baringin Siduampan (KSU-BS) caused, a change in the economy of the community in Jorong Siduampan which was the majority of the community's livelihood as rice farmers and after the existence of cooperatives most of the people planted oil palm and also caused the community's economy to improve. This research is a type of historical research that is composed of four stages, namely heuristics, source criticism, interpretation and writing. The results of this study indicate that: Koperasi Serba Usaha Baringin Siduampan s a cooperative unit formed in collaboration with PT. Bintaran Tani Nusantara (PT. BTN) which functions as an Engineering Advisor and avails. The first business unit was a plasma plantation and in 2007 it was the beginning of the plasma plantation harvest. In 2008 the cooperative established a cocoa drying business. In 2010, the business units that had been run were the plasma plantation business unit, the transportation unit, the cocoa drying business unit and savings and loan business unit. In 2012, the all-running cooperative business unit was a plasma plantation and transportation business unit. In 2015, the plasma plantation business unit and the transportation business unit and there were 3 units of old units sold and replaced with 2 new units